Co-culture Systems of Drug-Treated Acute Myeloid Leukemia Cells and T Cells for In Vitro and In Vivo Study - Yangchan Li; Rui Su; Jianjun Chen (STAR Protocols, 2020)
Summary: A combination of immunotherapy and chemotherapy strategies could strengthen antitumor effects. This protocol elucidates a robust method via co-culturing drug pre-treated acute myeloid leukemia cells with CD3+ T cells, derived from leukoreduction system chambers, for in vitro and in vivo study. We optimized several aspects of the procedures, including timing of drug treatment, quantification of tumor cells, and approach of combination of CD3+ T cells with drug treatment in vivo. This enables the readouts of the interplay between drugs and T cells.For complete details on the use and execution of this protocol, please refer to Su et al. (2020).